(untitled) (Cambridge, U.K., 1997)
The Companion is divided into four main sections, focusing on reception, genre, context, and form. This ground-breaking book not only provides a wealth of material for an informed reading but also offers fresh and sophisticated insights which point to the shape of Virgilian scholarship and criticism to come.
Keywords: Epic poetry, Latin,Pastoral poetry, Latin,Thơ ca Epic, La tinh; History and criticism,History and criticism,Lịch sử và phê bình